The Egg-Turning Technique on The Hatching Performance of Hybrid Duck Eggs - Subagja, Hariadi; Nadia, Zahrotul Aprilia; Ningsih, Niati (International Journal of Technology, Food and Agriculture, 2024)
This research aimed to determine different egg-turning techniques on the hatching performance of hybrid duck eggs. The materials for this research include water, hatching eggs of hybrid ducks, and manual hatching machines. This research used the T-test with 2 treatments and 6 replications, including T1 (swipe egg-turning) and T2 (manual egg-turning), each replication consisting of 10 hatched hybrid duck eggs. The parameters observed included the percentage of mortality, the percentage of hatchability, and the hatching weight of hybrid ducks. Analysis of the resulting data uses an analysis of variance (ANOVA) with the SPSS (Statistical Package for Social Science) application. Data that had significant differences were then tested further using the DMRT test (Duncan Multiple Range Test). The results showed that the egg-turning technique had no significant effect on the hatching performance of hybrid duck eggs, including mortality, hatchability, and hatching weight. The conclusion of the research was the regular turning times with differences in egg-turning techniques did not influence the hatchability of the duck hybrid.